2014
DOI: 10.1002/art.38745
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Zoster and Tofacitinib Therapy in Patients With Rheumatoid Arthritis

Abstract: ObjectivePatients with rheumatoid arthritis (RA) are at increased risk for herpes zoster (HZ) (i.e., shingles). The aim of this study was to determine whether treatment with tofacitinib increases the risk of HZ in patients with RA.MethodsHZ cases were identified as those reported by trial investigators from the databases of the phase II, phase III, and long-term extension (LTE) clinical trials in the Tofacitinib RA Development Program. Crude incidence rates (IRs) of HZ per 100 patient-years (with 95% confidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
189
3
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 305 publications
(239 citation statements)
references
References 41 publications
34
189
3
8
Order By: Relevance
“…Event types such as malignancies or opportunistic infections did not emerge with prolonged treatment. Herpes zoster infections were reported without evidence of a dose effect during the OLE period at incidence rates (2.3/100 patient-yrs) similar to those described in association with biologic DMARD in RA 7,8 . Laboratory abnormalities leading to discontinuation were uncommon.…”
Section: Discussionmentioning
confidence: 52%
“…Event types such as malignancies or opportunistic infections did not emerge with prolonged treatment. Herpes zoster infections were reported without evidence of a dose effect during the OLE period at incidence rates (2.3/100 patient-yrs) similar to those described in association with biologic DMARD in RA 7,8 . Laboratory abnormalities leading to discontinuation were uncommon.…”
Section: Discussionmentioning
confidence: 52%
“…ACR20, ACR50, and ACR70 response rates were sustained over time between Months 1 and 48 ( Figures 2A-C). At Month 1, ACR20, ACR50, and ACR70 response rates for patients were 72.5% (n = 2923/4032), 48.0% (n = 1937/4032), and 27.4% (n = 1104/4032), respectively; corresponding rates at Month 48 were 74.4% (n = 96/129), 49.6% (n = 64/129), and 34.1% (n = 44/129).…”
Section: Rheumatologymentioning
confidence: 97%
“…It is noteworthy that the rates of herpes zoster in the phase III cohorts of patients receiving placebo and adalimumab in the tofacitinib program were also higher than those in the literature overall 47,48 . Recently reported risk factor analyses have shown that Asian patients exposed to tofacitinib had a higher IR of herpes zoster infection 49 . The rate of herpes zoster infection did not appear to increase after longterm treatment and followup 48 .…”
Section: Rheumatologymentioning
confidence: 99%
See 1 more Smart Citation
“…In that study, renal transplant recipients received CsA or tacrolimus as well as azathioprine (AZA) or mycophenolate mofetil (MMF); liver transplant recipients received similar treatment to renal transplant patients, with the addition of solumedrol and prednisone; finally, heart and lung transplant patients received ATG, AZA or MMF, CsA or tacrolimus and prednisone. Recently, a greater rate of herpes zoster was also observed in patients treated with an oral JAK inhibitor (tofacitnib) for the treatment of rheumatoid arthritis [44]. Therefore, in this study we monitored SVV reactivation in latently infected RM undergoing immunosuppression using clinically relevant therapies.…”
Section: Introductionmentioning
confidence: 99%